Development of Modern Physics Learning Media Based on Interactive Web Using the PJBL Model to Improve Critical Thinking Skills: A Systematic Review - Aris Doyan; Susilawati Susilawati; Ahmad Harjono; Syarful Annam; Muhammad Ikhsan; Nuraini Rachma Ardianti; Syamsul Hakim (Jurnal Penelitian Pendidikan IPA, 2025)
Critical thinking skills are the ability to analyze and evaluate information used to draw valid conclusions. Critical thinking skills can be facilitated through learning with a interactive web-based learning media with project based learning (PjBL) model. This research aims to identify and analyze research trends of development of modern physics learning media based on interactive web using the PjBL model to improve critical thinking skills. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. However, in 2024 there will be a decline in the research trend on it. There are many documents in the form of articles, proceedings, chapters, preprints, edited books and monograph that discuss research about development of modern physics learning media based on interactive web using the PjBL model to improve critical thinking skills. Key words that are often used in research about it are collaboratin, communication, creativity, technology etc